(3Gdabg GdfGaYs - (3eMeO Hf jhSa Hf eMeO GdYdhqj GdMSfj CHh GdbGSe, fGUQ GdOjf, GdeOfj GdSeQbfOj,J (B556 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG CeOg GdCHO (B, (3bGd GdTjN ENhGfi QMece Gddg hSCdJehfi Cf CUhZ dce ai Gdabg cJGHkG fGaYkG s
(3BNQgG (B:s
(3hddGHf SHYI ef GKfi YTQ SgekG hdGdg C(B'(3de HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs